Proceedings of the 7th International Conference on Tangible, Embedded and Embodied Interaction 2013
DOI: 10.1145/2460625.2460669
|View full text |Cite
|
Sign up to set email alerts
|

Animate mobiles

Abstract: In this paper, we explore body language in mobile phones as a means of relational interaction. We describe a prototype that allows the simulation of proxemic reactions to the nearing hand of a user, ranging from affection to aversion, based on nearness-based input and shape change-based output. A user study is reported, which indicates that users were able to interpret the prototype's behavior drawing on animal parallels. It is concluded that proxemically reactive actuation may be a viable means of actively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…On the other hand, we think that the low frequency of product properties among the constructs raise optimism for complementary models of shape-change; models that emphasize the experience of such interfaces. A few earlier papers have explored dimensions related to some of those that we elicited (e.g., Hemmert and colleagues in [21,22]), but we believe the categorization of constructs in the present paper is the first systematic mapping of this space. Note that the repertory grid procedure does not automatically result in non-product properties; Hertzum et al [23] also used repertory grid interviews on interactive products and found many more product properties than we do.…”
Section: Relation To Other Models Of Shape-changementioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, we think that the low frequency of product properties among the constructs raise optimism for complementary models of shape-change; models that emphasize the experience of such interfaces. A few earlier papers have explored dimensions related to some of those that we elicited (e.g., Hemmert and colleagues in [21,22]), but we believe the categorization of constructs in the present paper is the first systematic mapping of this space. Note that the repertory grid procedure does not automatically result in non-product properties; Hertzum et al [23] also used repertory grid interviews on interactive products and found many more product properties than we do.…”
Section: Relation To Other Models Of Shape-changementioning
confidence: 98%
“…Energy, for instance, seems to concern movement speed as evidenced by constructs like Hasty and Calm. Territoriality relates to approach and avoidance behavior, and may be mapped indirectly to movement (like Hemmert et al [21,22] have done). How to map many of the other categories to shapes and transformations among shapes remains hard.…”
Section: Relation To Other Models Of Shape-changementioning
confidence: 99%
“…A few examples of SCI showcase the actuation mechanism, either fully or partly, and thereby indicating the possibility to transform. Examples include Animate Mobiles [20], see Figure 7, which consist of a transparent acrylic box with a visible servo motor inside. Another example is Amphorm [29], a Kinetic Sculpture where the actuators are visible between each of the transparent actuated layers.…”
Section: Actuation Mechanism Specifying Transformability Potentialmentioning
confidence: 99%
“…Some works explored biological motions [20] to express certain emotions of the interface. For instance, DEVA [7] presented excitement through ear wiggling, and Animate mobiles [15] moved up its head toward the user to show affection.…”
Section: Getting Inspirations From Users' Everyday Lifementioning
confidence: 99%